(untitled) (Letras, 2019)
This new approach to characterization in the Tragicomedia de Calisto y Melibea is developed through a perception of what its authors surely planned for. The subject is Lucrecia, maid to Melibea, generally thought of as a secondary character inspiring little interest for readers. I believe, to the contrary, that as the constant companion to a libidinous Melibea and her illicit affair with Calisto, but deciding to withhold this information from her employers, Pleberio and Alisa, Lucrecia plays a key role in the resulting tragedies. One result of her role as witness to the passionate lovemaking of the protagonists, Lucrecia herself becomes vividly aware of her own sexuality.